Racial and Ethnic Disparities in Current Asthma and Emergency Department Visits: Findings from the National Health Interview Survey, 2001–2010 - Oraka, Emeka (J Asthma, 2013)
OBJECTIVES: Racial/ethnic disparities in current asthma prevalence and medical care are a major public health concern. We examined the differences in asthma prevalence and morbidity among major racial/ethnic populations in the U.S. METHODS: We analyzed data from the 2001–2010 National Health Interview Survey for adults (≥18 years) and children and adolescents (<18 years). Outcome variables were current asthma prevalence, episodes and emergency department/urgent care center (ED/UCC) visits. We used multivariate logistic regression to calculate model-adjusted prevalence and risk ratios (ARR). RESULTS: In our study, 9.0% children and 7.2% adults had current asthma. Non-Hispanic black and Puerto Rican children were more likely to have current asthma (ARR 1.46, 1.66 respectively) and ED/UCC visits (ARR 1.61, 1.66, respectively) than non-Hispanic whites. Prevalence of asthma episodes did not differ significantly (P>0.05) among different race/ethnicities after adjusting for covariates. Among adults, Puerto Ricans were more likely to have current asthma (ARR 1.60) than non-Hispanic whites, and Non-Hispanic blacks (ARR 1.78) and Puerto Rican adults (ARR 1.71) reported ED/UCC visits more frequently than non-Hispanic whites. Adults and children who received emergency care for asthma in the past 12 months more frequently received multiple components of asthma management and control (e.g., taking long-term medication, having an asthma management plan) compared to those without emergency care. CONCLUSIONS: Racial/ethnic differences in current asthma prevalence persist among children and adults, but are most prominent among adults with asthma-related ED/UCC visits. Appropriate and effective asthma management and education may lead to better asthma control and reduce emergency care utilization.